Is stroke knowledge retained? Four-year longitudinal data of FAST Heroes campaign - Baskini, Maria; Tsakpounidou, Kalliopi; Van der Merwe, Jan; Keramydas, Christos; Proestopoulos, Maria; Proios, Hariklia (Frontiers in Communication, 2023)
Introduction: Educational stroke programs seem to increase awareness about stroke management. However, there is a speculation that actual stroke knowledge post mass campaign implementation remains poor. The aim of the present study was to evaluate stroke knowledge retention four years post Fast Heroes program implementation, an interactive stroke educational program, in school-aged children without any follow up during this time.Methods: Seventy-eight (n= 47 had attended the program four years ago and n=31 had never attended the program) school-aged children completed the age-adjusted online preparedness questionnaire during class four years post program implementation. The variables used to measure campaign effectiveness were knowledge of: i) stroke symptoms described in the FAST acronym (Face-Arm-Speech), ii) appropriate course of action (i.e. calling an ambulance), and iii) the European emergency number (i.e. 112).Results: In all questions, children that had attended the program had 14-81% greater chances to answer correctly.Discussion: There is still knowledge gain even four years post program implementation with no follow up during that time. The design of the campaign (i.e. 5-week duration, ageappropriate exercises, cartoon animations, song and dance elements, sentimentally driven activities and 3-layer education dissemination) facilitates long-term knowledge retention and may have led to the knowledge gains observed. Broad implementation potentially as part of the annual curriculum in schools can impact community stroke knowledge and should be considered.